The Role Play Learning Center Model: Strategies for Enhancing Children's Self-Confidence - Dhawil Ilmiyah Albirkiy, Nur; Farikhatin Bella, Leni; Ayu Safitri, Revilina; Aqyum, Zumrotus; Nur Santi, Evi (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2025)
Background of the study: The Role-Play Center Learning Model is a child-centered educational approach conducted through Circle Time and thematic learning centers. In the role-play center, children are encouraged to explore their abilities according to their interests and talents, stimulating various aspects of multiple intelligences through guided play. This approach is designed to foster not only cognitive growth but also emotional and social development in early learners. Aims and scope of paper: This study aims to investigate whether the implementation of the role-play center learning model at TK Darunnajah Kamal effectively supports the development of multiple intelligences and enhances children’s self-confidence. Methods: The study employed a qualitative field research design. Participants included the principal, the role-play center teacher, and students. Data collection techniques involved observation (focused on children's activities and the learning environment), in-depth interviews, and documentation. Data analysis was conducted using the Miles and Huberman interactive model, which includes data display and conclusion drawing. Results: The findings indicate that the role-play center at TK Darunnajah Kamal allows children the freedom to choose their own activities under the guidance of teachers. Most of the children demonstrated increased self-confidence during learning activities. They were able to express their desires without fear of making mistakes, showing progress in both autonomy and communication skills. Contribution: This study contributes to the field of early childhood education by providing evidence of the effectiveness of center-based learning in supporting multiple intelligences and self-confidence. It also offers practical implications for educators seeking to design more inclusive and empowering learning environments in early childhood settings.